Treatment of diuretic resistant cor pulmonale by continuous arteriovenous haemofiltration. - Rowe, P A (1988)
A woman with diuretic resistant cor pulmonale had 24 litres of fluid removed over four days by arteriovenous haemofiltration. She was discharged one week later and has remained ambulant and independent for one year.